2021
DOI: 10.1159/000512282
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Platelet Counts and Serum Levels of VEGF-A, PDGF-BB, and BDNF in Extremely Preterm Infants Developing Severe ROP

Abstract: Introduction: Thrombocytopenia has been identified as an independent risk factor for retinopathy of prematurity (ROP), although underlying mechanisms are unknown. In this study, the association of platelet count and serum platelet-derived factors with ROP was investigated. Methods: Data for 78 infants born at gestational age (GA) <28 weeks were included. Infants were classified as having no/mild ROP or severe ROP. Serum levels of vascular endothelial growth factor A, platelet-derived growth factor BB, and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 52 publications
1
35
0
Order By: Relevance
“…Because infants without ibuprofen were not included as controls, we could not confidently exclude a physiologically decrease in angiogenic factors studied. According to Hellgren et al, both the VEGF-A and PDGF-BB concentrations increased in the first weeks after birth ( 44 ), while both parameters dropped dramatically in the current study. Besides, these remarkable decreases occurred within 3–4 days.…”
Section: Discussionsupporting
confidence: 61%
“…Because infants without ibuprofen were not included as controls, we could not confidently exclude a physiologically decrease in angiogenic factors studied. According to Hellgren et al, both the VEGF-A and PDGF-BB concentrations increased in the first weeks after birth ( 44 ), while both parameters dropped dramatically in the current study. Besides, these remarkable decreases occurred within 3–4 days.…”
Section: Discussionsupporting
confidence: 61%
“…In the current study, using single-cell transcriptomics, we found that the ω-6 (AA) vs. ω-3 (DHA/EPA) diet had lower Igf1 and Igf1r levels in retinal neuronal cells, which was validated in total retinas with qPCR. The Igf1 signaling is essential in preserving retinal vascularization in Phase 1 ROP [ 72 , 73 , 74 , 75 , 76 , 77 ]. We also examined if ω-3 vs. ω-6 LCPUFA modulates the expression of genes involved in cell death; we found very mild changes in Bcl2, Bcl2l1, Bcl2l11 Casp , and Myc in the retinal clusters (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Insulin-Growth Factor 1 (IGF-1) IGF-1 is an important liver-derived growth factor and a key regulator of body growth and development [150,151]. In premature infants, persistent low circulating IGF-1 levels strongly correlate with ROP development [94,[152][153][154][155][156]. IGF-1 is critical for normal retinal vascularization as a lack of IGF-1 in mice prevents retinal vessel growth [152].…”
Section: Hormones 421 Adiponectin (Apn)mentioning
confidence: 99%
“…Increasing the number of patients in the study would also help evaluate the effects of IGF-1 on ROP with completion of the current phase 2b clinical trial using SHP607 (recombinant protein complex of IGF-1/IGFBP3) in preterm infants (ClinicalTrials.gov Identifier: NCT03253263). Moreover, recent investigations have also demonstrated that low circulating IGF-1 levels are correlated with low weekly platelet counts [156], which is associated with ROP progression in premature infants [160,161]. Platelet transfusions inhibit retinal neovascularization in OIR mice [160], suggesting that normalizing platelet levels and platelet-derived growth factors (IGF-1, VEGFA, PDGFBB [156]) might prevent ROP in premature infants.…”
Section: Hormones 421 Adiponectin (Apn)mentioning
confidence: 99%
See 1 more Smart Citation